A study on the level of understanding among insurance practitioners towards the basic principles of insurance / Azizul Mohamad Nor - Mohamad Nor, Azizul (Faculty of Business and Management, 2010)
Insurance contract is a normal contract with the addition of its own unique principal.Improper understanding of the insurance principles may lead to the different interpretations that may result in unnecessary problems such as disputes, unnecessary claims, and even litigation. Thus, to attain a sound insurance practice all insurance practitioners must have the knowledge and understanding of the basic insurance principle before entering into the industry. This study is conducted to identify the level of understanding among insurance practitioners toward the basic principle of insurance. A set of questionnaire was randomly distributed to 60 respondents in collecting the data. The questionnaire is designed to test the respondent understanding towards the basic insurance principles. The independent variables are duration of working experience, insurance practitioner’s level of education, and type of insurance organization that insurance practitioner currently employed. Likert scale is used in most questions as it is used to determine the level of understanding how strongly agree or strongly disagree of the respondent with the statement regarding the principles. As the conclusion of this study, this report presents the results of the study related to the issue of insurance practitioners’ level of understanding towards the six basic insurance principles.